2016
DOI: 10.1063/1.4943719
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and structural properties of polymer composites filled with activated charcoal particles

Abstract: Abstract.We have studied the molecular properties, structural properties, and chemical composition of composites by Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD) spectroscopy, and X-ray fluorescence (XRF) spectroscopy, respectively. FTIR spectra shows absorption band of hydroxyl group (-OH), methyl group (-CH 3 ) and aromatic group (C-C). The absorption band for aromatic group (C-C) shows the formation of carbonaceous in composites. XRF shows chemical composition of composites, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…The shifting of peaks to higher wavenumber and appearance of new peaks showed successful adsorption of the heavy metals [33] and may be due to the interaction of the heavy metals with the functional group [34]. The absorption band at 1578 cm -1 arising from aromatic group (C-C), is indicating the formation of carbonaceous material [31]. Table 2 shows the functional groups on the FTIR peak positions and their vibration forms.…”
Section: Ftir Analysismentioning
confidence: 97%
See 2 more Smart Citations
“…The shifting of peaks to higher wavenumber and appearance of new peaks showed successful adsorption of the heavy metals [33] and may be due to the interaction of the heavy metals with the functional group [34]. The absorption band at 1578 cm -1 arising from aromatic group (C-C), is indicating the formation of carbonaceous material [31]. Table 2 shows the functional groups on the FTIR peak positions and their vibration forms.…”
Section: Ftir Analysismentioning
confidence: 97%
“…The importance of the knowledge of the LOI can also be employed as an indicator in monitoring the quality of the final product, it is the amount of weight loss through raising the temperature of the material to a predetermined level [28]. Many studies showed the loss on ignition by EDXRF spectroscopy [29][30][31]. Characterization of the ZnO/activated carbon nanocomposites in Cd sequestration was reported [15] for FTIR, SEM and XRD without elemental study.…”
Section: Elemental Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Carbon composites have become a crucial component in modern technology, with numerous applications in military, civilian, energy, medical, and environmental fields. Polymer composites, made with affordable materials and equipment, are easy to produce and offer both process ability and cost-effectiveness [5][6][7].Composite materials are produced by combining or merging different materials or qualities in which the component elements are individually distinct, or, two or more phases combined physically, which result in a new material that has excellent features if compared to the features of the individual phases [8][9][10].In opposing to alloys, every phase of composites keeps its distinguished physical, mechanical, and chemical properties [9,11,12].The essential utilities of composites are good stiffness, high specific strength, and good electrical and thermal properties results. In addition to lightweights when they are compared with alloys or ceramics products [13,14].…”
Section: Introductionmentioning
confidence: 99%